2008
DOI: 10.1590/s1020-49892008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Toxoplasma gondii infection among pregnant women in Trinidad and Tobago

Abstract: In Trinidad and Tobago, the seroprevalence of past infection by T. gondii in pregnant women is relatively low (39.3%) for patients in both hospital and health center clinics. Consequently, there is an elevated risk of primary infection during pregnancy and the potential for congenital infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
5
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
5
5
3
Order By: Relevance
“…Studies conducted in China describe a seroprevalence variation with location (rural vs. urban) with a higher prevalence in the countryside (12·7% vs. 7·5%) [30]. In contrast, Ramsewak et al [28] could not corroborate these findings.…”
Section: Risk Factors Evaluation: Lisbon (Portugal) and Luanda (Angola)mentioning
confidence: 84%
See 1 more Smart Citation
“…Studies conducted in China describe a seroprevalence variation with location (rural vs. urban) with a higher prevalence in the countryside (12·7% vs. 7·5%) [30]. In contrast, Ramsewak et al [28] could not corroborate these findings.…”
Section: Risk Factors Evaluation: Lisbon (Portugal) and Luanda (Angola)mentioning
confidence: 84%
“…The pregnant women with >2 births had increased chance of a seropositive diagnosis compared to those with only one birth (Table 3). Although, it was expected that multiparous women would have knowledge of toxoplasmosis prevention measures, in a study by Ramsewak et al [28] in the region of Trinidad and Tobago, it was found that there was an increase in prevalence of IgG/IgM antibodies to T. gondii in pregnant women who had more than three children than in the other groups. However, Porto et al [29] did not corroborate these findings in pregnant women from Brazil.…”
Section: Risk Factors Evaluation: Lisbon (Portugal) and Luanda (Angola)mentioning
confidence: 99%
“…Literatürde IgG seroprevalansının yüksek bulunduğu çalışmalarda yeni enfeksiyonların tespit edilebilmesi açısından gebelik döneminde rutin serolojik taramaların yapılması önerilmektedir (16,18 bulunduğu çalışmalarda ise hamilelik döneminde enfeksiyonla ilk kez karşılaşma riskinin daha yüksek olduğu ve konjenital enfeksiyon gelişmesi riski nedeniyle gebelerde tarama yapılmasının önemli olduğu bildirilmiştir (10). Ayrıca, evde kedi besleme, çiğ sebze tüketimi, çalışma yeri, gebelik gibi risk faktörlerinin enfeksiyonla ilişkili bulunduğu çalışmalarda da hamile kadınların gebelik öncesinde koruyucu eğitim almalarının ve gebelik süresince takip edilmelerinin enfeksiyonun önlenmesinde önemli rol oynadığı bildirilmiştir (6,7).…”
Section: Discussionunclassified
“…Hamilelikte primer toxoplasmosis geliştiğinde şiddetli patolojik defektlere (düşük, ölü doğum, fetal anomali; hidrosefali, koryoretinit vb) yol açabilen konjenital toksoplazmoz gelişebilmektedir (2,(5)(6)(7)(8). Dünyada gebelerde yapılan çalışmalarda T.gondii IgG antikor seroprevalansının %20,3 ile %79,8 arasında değiştiği görülmektedir (6,7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Bu farklılık, bölgesel risk faktörlerinin çeşitlilik göstermesinden kaynaklanmaktadır.…”
Section: Introductionunclassified
“…Es un parásito protozoario intracelular obligado de la familia Apicomplexa, orden Coccidia, el cual recibe su nombre por el complejo apical de su citoesqueleto 23 . Su hospedero definitivo son los felinos, teniendo una amplia variedad de potenciales hospederos intermediarios, tales como: humanos, mamíferos no felinos, aves 12 ; animales domésticos o de granja por ejemplo: cerdos, ovinos, caprinos, bovinos, equinos, perros y pollos, así también animales salvajes como monos, aves migratorias y diferentes depredadores 24 .…”
Section: El Agente Causalunclassified